Cry in the Wilderness: Depiction of Tribals in Select Malayalam Films - Cherian, Rajesh; Gireesh J. (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
The marginalization of tribals not just from mainstream society but also from the cultural realm has always been an intensely debated topic. This article seeks to explore their representation in Malayalam films and how it has been historically shaped by dominant social and cultural factors rather than by lived reality. Drawing on selected films like Aranyakam, Bamboo Boys and Narivetta the study examines the politics of representation and how it has critically contributed to the construction of stereotypical images of the tribal community.